Active Learning Inspired by Team-Based Learning and Project-Based Learning - Montes Granado, Consuelo (Opción, 2015)
When learning content knowledge is not enough in an academic subject, knowledge application becomes the teaching goal. Using the Team-Based Learning approach has proved to be an excellent instructional method for this purpose. The aim of this article is to present a design I have devised for the subject of Pragmatics exploring TBL’s pedagogical potential. My research is enriched exploring the insight of Project-Based Learning: choosing challenging taks. I have used a descriptive-comparative methodology for my design’s premises, and the qualitative method of supporting my claims with my students’ reflective appraisals. Results: the pedagogical values and success of this design.